Infective endocarditis: incidence and mortality in the North East Thames Region. Issue 1 (January 1988) - Skehan, J D; Murray, M; Mills, P G
Abstract : A survey of infective endocarditis in the North East Thames Regional Health Authority was carried out over a period of 30 months from 1982 to 1984. The incidence, clinical characteristics, and in-hospital mortality were studied. Important causes of endocarditis were dental treatment, the presence of dental disease, drug abuse, and cytoscopy. The omission or incorrect administration of antibiotic prophylaxis in patients with valve disease was noted, but failure of correctly prescribed antibiotic prophylaxis was not recorded. Adverse prognostic features were increased age, prosthetic valve infection, Gram negative or staphylococcal infections, and aortic valve involvement. In contrast, mortality was lower in patients with mitral valve prolapse, ventricular septal defect, and streptococcus viridans infection. Deaths were usually attributable to irreversible complications present at the time of diagnosis. Vegetations were detected on the echocardiogram in half of those studied and mortality was higher in those with vegetations than without. Operation for native valve infection was associated with a low mortality and it is likely that the overall mortality for infective endocarditis has been improved by surgical intervention.